Marketing Mix Strategy Development of Ban Lai Kaew Karen Weaving Textile Group, Chiang Mai Province - Pichayakul, Pichayalak; Mahachaiwong, Nittaya; Srisawat, Jermkuan (Area Based Development Research Journal, 2020)
This research aims to develop a marketing mix strategy of Ban Lai Kaew Karen Weaving Textile Group, Chiang Mai province. The researchers applied Strategic Management of Marketing Mix concept and Participatory Action Research (PAR). The research was conducted in collaboration with members of Ban Lai Kaew Karen Weaving Textile Group, Doi Tao district, Chiang Mai province during 2016 – 2017. The proactive-marketing mix strategies implemented in the community consist of 1) Transforming the existing products to new products which possess Pwo Karen identity and developed 3 new product categories which include scarves weaved with thinner cotton thread and Eri silk thread, big bags, and small bags made of the community’s weaving textile as raw material; 2) Setting higher prices and expanding into the middle and upper market segment; 3) Expanding marketing distribution channels by joining trade shows and selling in consignment stores; and 4) Promoting via television programs, magazines, and Facebook Fanpage. The proactive-marketing mix strategies result in higher income of Ban Lai Kaew Karen Weaving Textile Group from THB 336,000 to THB 715,000 per year, or an increase by 112.80%. Finally, the group is empowered to preserve the community old traditions and interest the public in visiting the Karen Weaving Textile Cultural Learning Center.